Physical model test on the sealing mechanism and reinforcement effect of flowing water grouting for water-sand mixture inrush in the Cuihongshan iron-polymetallic mine - Baofu WU; Wanghua SUI; Guilei HAN; Longfei LIANG; Xinhai YAO; Jiaxin FENG; Xingshuo XU (Shuiwen dizhi gongcheng dizhi)
Under flowing-water conditions, water-sand mixture inrush in metal mines are highly destructive and sudden, posing a significant threat to mine safety. Effective and reliable treatment technologies remain underdeveloped. This study utilized a physical model, to visualize the grouting process and acquire relevant data, with the aim of investigating the diffusion, filling, and consolidation characteristics of grout in fractured rock masses under flowing-water conditions at the Cuihongshan iron polymetallic mine, and validating and optimizing a cement-sodium silicate two-liquid grouting system. Results demonstrate that grouting sequence significantly influences grout diffusion rate and extent. Early-stage grouting exhibites rapid diffusion but low consolidation ratios. The three grouting stages (Z1, Z2, and Z3) sequentially presente ascending, arched, and basin-shaped patterns with consolidation ratios of 50%, 80%, and 90%, respectively. The Z1 and Z2 stages presente a slow-fast-slow grouting rate pattern, whereas Z3 exhibited slow, uniform diffusion and filling, confirming the necessity of secondary borehole grouting. Soil pressure increases correlated positively with grouting pressure, volume, and depth, with an average increase of 724 kPa after grouting. Osmotic pressure increases by averages of 1.91 kPa, 1.45 kPa, and 0.57 kPa, respectively, exhibiting a multi-peak pattern in Z1 and Z2 and a plateau pattern in Z3, indicating significant water sealing and reinforcement effects. Complete water blockage is achieved in the Z2 stage, transitioning the grouting environment to static conditions and suggesting a necessary adjustment to field treatment strategies. Based on pressure similarity ratios, the maximum grouting pressures for primary and secondary boreholes in field applications are determined to be 0.5 MPa and 0.3 MPa, respectively. Key criteria for evaluating grouting effectiveness are established. The grouting pressure and flow-rate trends observed in field applications closely match the model test results, and multiple evaluation indicators confirm that treatment efficacy meet the engineering design requirements. This study validates the precise guidance provided by the experimental model for field treatment and offers essential theoretical and technical support for treating water-sand mixture inrush in metal mines.